MANAJEMEN LIMBAH DI TEMPAT PENGOLAHAN AKHIR MANGGAR - rusba, komeyni; Sari, Iin Pratama; Mulya, Widya; Purwanti, Sri (Program Studi D4 K3 Universitas Balikpapan, 2023)
TPA Manggar is a facility owned by the Balikpapan City Government which stands on an area of ​​27.1 hectares on Jalan Proklamasi RT. 36. On January 13, 2012, TPA Manggar was officially operational and until now it continues to beautify itself so that it is not just a garbage collection site. The purpose of carrying out the activity. are as follows: Improving the quality and continuity of student activities at the University of Balikpapan in the community in order to create a strong, independent and prosperous society. Increase the understanding of lecturers, students, the community, and partners about sustainable development at the Manggar Waste Landfill in Balikpapan. Promoting the Balikpapan University program as a vehicle for solving problems based on local wisdom and potential as well as partnerships with the community, government and other stakeholders. Improving the quality and breadth of partnership networks in community empowerment through the activities of Balikpapan University students. TPA Manggar has an important function as a place for final disposal of waste in the city of Balikpapan, besides that TPA Manggar has functions from an economic and academic perspective such as tourism development as well as an educational place. This is a potential for TPA Manggar.